Desenvolvimento de nano e micropartículas de quitosana encapsulando 4-metilesculetina e avaliação no tratamento da doença inflamatória intestinal - Masago, Fabiana [UNESP] (2015)
Ulcerative colitis and Crohn's disease, the main forms of Inflammatory Bowel Disease (IBD), are chronic diseases which cause abdominal pain, diarrhea and bleeding. Nowadays, the available treatments, such as aminosalicylates, glucocorticoids, immunosuppressants and biological therapy with monoclonal antibodies do not promote a definitive cure; furthermore, they are associated with several side effects. Recent studies showed protective effects of coumarin derivative 4-methylesculetin (4-ME) against colonic inflammation induced by 2,4,6-trinitrobenzenesulphonic acid (TNBS), which was associated to the anti-inflammatory and antioxidant properties of 4-ME. Since encapsulation of drugs and active products into nano and microparticles are able to increase the retention time in the colon and improve pharmacology activity; the present study aims to develop chitosan nano and microparticles containing 4-ME, and to evaluate if these pharmaceutical formulations improve intestinal anti-inflammatory activity 4-ME when compared to its free form. For this, nano and microparticles of chitosan with 4-ME encapsulated were standardized, which were administered, by oral route, at the dose of 5 mg/Kg, and its effects compared with same dose of free form of 4-ME, using the TNBS model of colonic inflammation in rats. In this context, macroscopic (score, lesion extension, weight/length ratio and adherence) and biochemical (myeloperoxidase and alkaline phosphatase activities and total glutathione content) parameters were analyzed. Treatments with nano and microparticles were not able to minimize TNBS-induced inflammation; however, free form 4-ME demonstrated anti-inflammatory activity evidenced by the significant inhibition of alkaline phosphatase activity and counteraction of glutathione depletion. In conclusion, 4-ME associated with nano and microparticles of chitosan did not represent an appropriated pharmacologic strategy for the controlled delivery of 4-ME ...